SOME REFLECTIONS ON THE RELIGIOUS ARCHITECTURE OF CHACH IN ANTIQUITY AND THE EARLY MIDDLE AGES - Normurodov D. R. (TARIXIY TADQIQOTLAR, 2025)
The article analyzes the architectural structures of the Chach oasis built in the Antiquity and Early Middle Ages for performing religious rituals, as well as ceremonies dedicated to the sun, fire, and the commemoration of ancestors. It also highlights the emergence, spread, and integration with local traditions of crossshaped and rectangular-plan structures, as well as domestic sanctuaries intended for cult practices in Chach and the surrounding regions. It is noted that the ritual sites of Chach, similar to those in various historical and cultural regions of Central Asia, were adapted to family and communal ceremonies, had distinctive features, harmonized with the temples of Sogd, Bactria, Khorezm, and Fergana, and further developed under local conditions.